The Effect of Perceived Discrimination on Social Alienation of Probationers: Evidence from China - Xu, Tun (The prison journal, 2023)
Applying an integrated mode of labeling theory, this study conducted an empirical analysis of 427 probationers from 48 judicial offices in China. The results found that, after controlling for age, gender, educational background, marital status, and social support, perceived discrimination is positively correlated with social alienation; shame plays a partial positive mediating role in the relationship between perceived discrimination and social alienation. Additionally, Zhongyong thinking can moderate the direct effect of perceived discrimination on social alienation and the mediating effect of shame in a negative way. The results further empirically validated an integrated model of labeling theory.